The POTRAYAL OF ENGLISH TEACHING AT SMA HANG TUAH 4 SURABAYA - Tri Achmad, Efendi (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2023)
Teaching activities are the main part of the process of teaching and learning. Therefore, the researcher was interested in finding out what activities were employed in the classroom. To find the answer, there was an English teacher as a participant in this study who taught more than three classes. This study used a qualitative method with a questionnaire, an interview, and observation as the research instruments. The questionnaire was derived from theories of English teaching methods and was used to gather data on the teaching activities applied in her classroom. Then, the observations were done to see the actual teaching and learning process in the classroom. At last, the interview was conducted to enrich the data and clarify what was found in the questionnaire and observations. The findings showed that the teacher stated in the questionnaire and interview that she used various teaching techniques. However, it was found that translation, reading aloud, grammar explanation, and exercises were mainly done. It implied that traditional teaching methods like the Grammar Translation Method are still implemented in our classroom. This kind of method focuses on what to teach; as its characters and principles show, it does not teach students how to use the language.